The carbon footprint of Conservation Agriculture - Maik Freitag; Theodor Friedrich; Amir Kassam (International Journal of Agricultural Sustainability)
Proponents of Conservation Agriculture (CA) believe that by not tilling the soil, climate-friendly agriculture is achieved by reducing greenhouse gas emissions from agriculture and by storing atmospheric carbon in the soil. However, some scientists question climate benefits of CA. Literature shows that carbon storage through soil organic carbon (SOC) accumulation of up to 1 t ha–1 y–1 is possible without increasing nitrous oxide (N2O) emissions under a CA system. Opposing studies were flawed by analysing not complete CA systems and leaving out some of the principles. It is shown that each tillage operation releases up to 300 kg carbon dioxide equivalents (CO2e) per hectare, and each of the average annual 10 t ha–1 of eroded topsoil can emit additional 300 kg CO2e ha–1. A case study in Germany confirms these findings that with full application of CA the carbon footprint of agricultural food production can be significantly decreased, helping to mitigate climate change. It is concluded that net soil carbon storage is possible if all the principles of CA are consistently implemented. It is also concluded that together with other complementary production measures, CA has the potential to make agriculture carbon neutral.